Peran Keterikatan Merek dalam Memediasi Pengaruh Citra Merek terhadap Niat Beli Ulang (Studi pada Pelanggan Parfum Merek HMNS di Kota Denpasar) - Razheva Rayya Husein; Ni Wayan Sri Suprapti (Penerbit Jurnal Indonesia, 2026)
The increasing competition in the local perfume industry in Indonesia requires brand strategies not only to build a strong brand image but also to create emotional attachment in order to maintain customer loyalty. HMNS is one of local perfume brands that has a strong brand image through a storytelling approach and emotional values; however, it still needs to strengthen its strategy to encourage customers' repurchase intention. This study seeks to examine role of brand attachment as a mediating variable in relationship between brand image and repurchase intention among customers of HMNS perfume in Denpasar City. The data were collected involving brand, selected using a purposive sampling method. Hypothesis testing was conducted using path analysis. The findings indicate that brand image does not directly have a positive significant influence on repurchase intention. However, brand image is shown to have a positive significant effect on brand attachment. Furthermore, brand attachment significantly positively influences repurchase intention. The results also confirm that brand attachment fully mediates the relationship between brand image and repurchase intention among HMNS perfume customers in Denpasar City. These results suggest brand image alone isn’t enough to directly drive customers to make repeat purchases. Instead, a strong brand image can strengthen customers’ emotional connection to the brand, which then leads to increased repurchase intention. Therefore, companies should focus on enhancing brand image in a way that fosters emotional attachment, so customers not only recognize the brand but also feel connected to it and are more likely to continue purchasing it repeatedly.